x-1=cx+d (c can't equal to 1)
This is what I did:
I moved the x to the other side so its going to be -1=(cx-x)+d
-1=bx+d
-d-1/b=x
…the previous one that I did was ax+b=c (a cannot equal to 0). I moved the b to the other side so I had b-c=ax. Then I moved the a to the other side by canceling it out with another a. So my final answer was (b-c)/a=x.
I got the b by subtracting cx-x. I thought it would be b since its alphabetical order and since it has a negative it would go one backwards. Dont know if I explained myself correctly lol.
JeffM beat me to it, but I'll add my two cents, in case that helps any.
First of all, it is incorrect to insert new variables (b) into this type of problem. Secondly, there is no rule/tradition in math regarding “alphabetical order and since it has a negative it would go one backwards.”
More to the point, let’s discuss some fundamentals. When we talk about moving something from one side of an equation to the other, we are being a little lax in stating what we are actually doing. What we are doing is performing a mathematical operation, in this case subtracting the same thing from both sides of the equation. I think it would be very useful to you to stop saying you are “moving” a variable from one side to the other. Instead say you are subtracting/adding/multiplying/dividing both sides of the equation in the same way. For example,
ax+b=c
First, subtract b from both sides of the equation and simplify:
ax + b – b = c – b
ax = c - b
Second, divide both sides of the equation by “a” and simplify:
(ax)/a = (c – b)/a
x = (c – b)/a
You will notice that I got a different answer than you did. Mine has “c – b” in the numerator while yours has “b – c”. This is likely because you “moved b over", rather than “subtracted b from both sides of the equation.” Your imprecise way of thinking about the mathematical operation resulted in an incorrect sign change.
Now, on to your current problem:
x-1=cx+d
-1=(cx-x)+d
You have correctly subtracted x from both sides of the equation (though there are other sequences of steps that will work). You have two terms – cx and x – that both have x as a factor. Therefore you can factor x out and rewrite your equation:
-1 = x(c – 1) + d
Next, subtract d from both sides. Then divide both sides by (c – 1):
-1 – d = x(c – 1)
(-1 – d)/(c – 1) = x
You have now solved for x. This result can also be written in the following ways:
x = (-1 – d)/(c – 1) = -(1 + d)/(c – 1) = (1 + d)/(1 – c)